Beta-alanine supplementation improves the relaxation speed of in-vivo fresh and fatigued skeletal muscle - Stannard, R. L.; Barnett, C. T.; Davidson, J.; Maritza, B.; Fraser, W. D.; Harris, R.; Sale, C. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
PURPOSE: In fresh muscle, supplementation with the rate-limiting precursor of carnosine, beta-alanine (BA), results in a decline in muscle half-relaxation time (HRT) potentially via alterations to calcium (Ca2+) handling. Accumulation of H+ has been shown to impact Ca2+ signalling during muscular contraction and carnosine has the potential to serve as a cytoplasmic regulator of Ca2+ and H+ coupling, since it competitively binds to both ions. The present study examined the effect of BA supplementation on intrinsic in-vivo knee extensor force production and muscle contractility in both fresh and fatigued human skeletal muscle assessed during voluntary and electricallyevoked (nerve and superficial muscle stimulation) contractions. METHODS: Twenty-three males completed two experimental sessions, pre- and post- 28 days supplementation with 6.4 g.day-1 of BA (n=12; age, 22 ± 2 years, height, 1.80 ± 0.05 m, body mass, 76.0 ± 7.3 kg, MVIC, 565 ± 86N) or placebo (PLA; n=11; age, 22 ± 1 years, height, 1.83 ± 0.06 m, body mass, 81.4 ± 14.2 kg, MVIC, 600 ± 149N). The Institutional Ethical Review Committee approved the study. Force was recorded during a series of voluntary and electrically evoked knee extensor contractions. RESULTS: BA supplementation had no effects on voluntary or evoked force production, or twitch electromechanical delay and time-to-peak tension. Nonetheless there was a decline in muscle HRT in fresh and fatigued muscle during both resting (3 ± 13%; 19 ± 26%) and potentiated (1 ± 15%; 2 ± 20%) twitch contractions. CONCLUSION: The key findings from the present study are a) no effects of BA supplementation on force production capacity in either fresh or fatigued skeletal muscle, b) the confirmation of our previous findings (Hannah et al. 2015) showing enhanced fresh muscle relaxation speed following 28 days of BA supplementation and c) that the skeletal muscle relaxation speed is also reduced by BA supplementation following muscle fatigue (H+ accumulation) in the absence of any change to peak force production or contraction time. The mechanism for reduced HRT in fresh and fatigued muscle following BA supplementation is unclear. Due to the importance of muscle relaxation on total energy consumption, especially during short, repeated contractions, BA supplementation may prove to be beneficial. These data are the first to comprehensively examine the effect of BA supplementation on voluntary and electrically evoked contractile properties of in-vivo fatigued human skeletal muscle.